2020
DOI: 10.3892/etm.2020.9557
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of glutathione as a treatment for Parkinson's disease

Abstract: The quality of the included articles was assessed using the bias risk assessment tool of the Cochrane systematic evaluator manual (version 5.1.0). Pooled analysis of the relevant data was performed using RevMan 5.3 software and subgroup analysis was performed to determine the impact of the dosage (300 vs. 600 mg) on the outcome measures. A total of seven randomized controlled trials involving 450 participants were included in the meta-analysis. The results of the present study indicated a statistically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…For example, ERGO and GSH are maintained at high levels in erythrocytes likely due to their ability to maintain haemoglobin in its active and reduced form. Also, both ERGO and GSH have been implicated in the pathogenesis of neurodegenerative diseases such as Alzheimer's disease [14,15] and Parkinson's disease [16][17][18]; these effects have been targeted for the development of potential therapeutic strategies [19].…”
Section: Ergothioneine Content In Foodmentioning
confidence: 99%
“…For example, ERGO and GSH are maintained at high levels in erythrocytes likely due to their ability to maintain haemoglobin in its active and reduced form. Also, both ERGO and GSH have been implicated in the pathogenesis of neurodegenerative diseases such as Alzheimer's disease [14,15] and Parkinson's disease [16][17][18]; these effects have been targeted for the development of potential therapeutic strategies [19].…”
Section: Ergothioneine Content In Foodmentioning
confidence: 99%
“…Furthermore, MDS-UPDRS scores increased in four of the five PD patients treated with oral NAC, a worsening of clinical parameters which the authors suggested may have occurred due to drug-drug interactions between NAC and other PD medications, such as amantadine [87]. A recent meta-analysis, which considered both intranasal and intravenous administration of GSH identified a statistically significant increase in glutathione peroxidase levels as well as an improvement in section III, the motor examination component of the under the revised MDS-UPDRS criteria [88]. Interestingly, the authors also performed a subgroup analysis [88] which found that 300 mg/d GSH was more effective than 600 mg/d in reducing MDS-UPDRS III scores.…”
Section: Glutathionementioning
confidence: 93%
“…A recent meta-analysis, which considered both intranasal and intravenous administration of GSH identified a statistically significant increase in glutathione peroxidase levels as well as an improvement in section III, the motor examination component of the under the revised MDS-UPDRS criteria [88]. Interestingly, the authors also performed a subgroup analysis [88] which found that 300 mg/d GSH was more effective than 600 mg/d in reducing MDS-UPDRS III scores. However, there is significant variation in both the dose and method of administration in clinical trials of GSH and further research is necessary to investigate both the optimal treatment strategy as well as to confirm any clinical benefit identified.…”
Section: Glutathionementioning
confidence: 99%
“…It has garnered significant attention for its potent antioxidant properties since it acts as a detoxifier of free radicals and helps regulate ROS balance [ 14 , 15 ]. Numerous studies show the effectiveness of GSH in neurones, skin, and other tissues [ 16 , 17 ]. Notably, GSH has promising effects in liver diseases [ 18 ].…”
Section: Introductionmentioning
confidence: 99%